Research on brand extension feedback effects based on customer equity - J. Shao; J. Zhang; K. Chen (South African Journal of Business Management, 2015)
As a strategy for enterprises to expand the scale of their operations, brand extension could also generate feedback effect diluting parent brand's customer equity. This study proposes and estimates a theoretical model examining the influence of brand extension on the drivers of parent brand's customer equity, namely value equity, brand equity, and retention equity using data of 850 questionnaires from ordinary consumers in China. The model indicates whether the drivers of a parent brand's customer equity change after brand extension, and how fit and consumer evaluations of brand extension influence the drivers of the parent brand's customer equity. The results show that firstly brand extension influences the drivers of parent brand's customer equity, secondly fit and consumer evaluations of brand extension directly affect the drivers of parent brand's customer equity, consumer evaluations also perform an intermediary function between fit and the drivers of parent brand's customer equity. Finally, this paper talks about managerial implications of the finding.Limitations and suggestions for future research are also discussed.
Keywords: 650